Branding Kota dan Tipologi Arsitektur dalam Mengembangkan Wajah Kota Tuban - Martino Dwi Nugroho; Ivada Ariyani (Institut Seni Indonesia Yogyakarta, 2025)
Penelitian ini bertujuan untuk merumuskan identitas arsitektur perkotaan yang mencerminkan karakter khas Kabupaten Tuban sehingga dapat mendukung peningkatan potensi destinasi pariwisata dan mendorong pembangunan ekonomi daerah. Selain itu, penelitian ini juga dimaksudkan untuk menyusun panduan awal dalam penataan ruang dan tampilan kota secara arsitektural agar mampu menjaga serta memperkuat kekhasan visual dan budaya yang dimiliki Kabupaten Tuban. Metode yang digunakan dalam penelitian ini adalah dengan metode design thinking. Adapun hasil yang dicapai dalam penelitian adalah desain untuk penanda kota seperti bentuk gapura paduraksa dan bentar yang berciri khas Tuban, bentuk atap pendapa di kantor pemerintahan Kabupaten Tuban, penerapan batik Gedog pada fasad bangunan, landmark Kota Tuban, logo Kota Tuban sebagai penanda di Alun-Alun Kota Tuban, dan street furniture. Unsur-unsur sejarah kota Tuban menjadi pertimbangan dalam pengembangan desain, di antaranya adalah gapura makam Sunan Bonang; arsitektur tradisional Jawa, yaitu atap sirap, yang mengambil unsur dari rumah jaman Majapahit; arsitektur Klenteng, arsitektur kolonial, dan Kuda Ronggolawe. Rekomendasi dari penelitian ini adalah keberlanjutan dari desain yang akan diterapkan di seluruh wilayah Kabupaten Tuban, dari tingkat kelurahan hingga ke kabupaten/Kota. This activity aims to formulate an urban architectural identity that reflects the distinctive character of Tuban Regency in order to support the development of both potential tourism destinations and regional economy. It is also intended to compile initial guidelines in spatial planning and architectural appearance of the city to preserve and strengthen the visual and cultural uniqueness of Tuban. The authors implemented the Design Thinking method. The activity results the designs for city icons such as the shape of the Paduraksa and Bentar gates, the shape of the pendapa roof in Tuban Regency government office, the application of Gedog batik on building facades, the landmarks, the Tuban City Logo at the town square, and the street furniture. The historical elements of Tuban are incorporated in the design, including the gate of Sunan Bonang's tomb, traditional Javanese architecture, particularly shingle roofs derived from Majapahit era’s houses, Klenteng architecture, and Colonial Architecture. The recommendation from this program is the sustainability of the design that will be implemented throughout Tuban Regency, from the sub-district level to the district/city level.This study aims to formulate an urban architectural identity that reflects the distinctive character of Tuban Regency, so that it can support the increase in potential tourism destinations and encourage regional economic development. In addition, this study is also intended to compile initial guidelines in spatial planning and architectural appearance of the city in order to maintain and strengthen the visual and cultural uniqueness of Tuban Regency. The method used in this study is the Design Thinking method. The results achieved in the study are designs for city markers such as the shape of the paduraksa and bentar gates that are characteristic of Tuban, the shape of the pendapa roof in the Tuban Regency government office, the application of Gedog batik on building facades, Tuban City landmarks, the Tuban City Logo as a marker in the Tuban city square, and street furniture. The historical elements of Tuban city are considered in the development of the design, including the gate of Sunan Bonang's tomb, traditional Javanese architecture, namely shingle roofs that take elements from Majapahit era houses, Klenteng architecture, and Colonial Architecture. The recommendation from this research is the sustainability of the design that will be implemented throughout Tuban Regency, from the sub-district level to the district/city level.